Potential Utility of Systemic Plasma Biomarkers for Evaluation of Pediatric Schistosomiasis in Western Kenya - Ondigo, Bartholomew N.; Hamilton, Rachael E.; Magomere, Edwin O.; Onkanga, Isaac O.; Mwinzi, Pauline N.; Odiere, Maurice R.; Ganley-Leal, Lisa (Frontiers in Immunology, 2022)
Introduction Current diagnostic tools for schistosomiasis are limited, and new tests are necessary to enhance disease diagnosis and surveillance. Identification of novel disease-specific biomarkers may facilitate the development of such tests. We evaluated a panel of biomarkers used in sepsis and parasitic diseases for their potential suitability in the diagnosis of schistosomiasis. Objective The study evaluated the levels of systemic plasma biomarkers in relation to Schistosoma mansoni infection and parasite burden. Methods Six biomarkers were measured in the plasma of children from schistosomiasis-endemic regions using ELISA. The concentration of soluble CD23 (sCD23) and lipopolysaccharide (LPS) was tested in 199 and 124 plasma samples, respectively, while interleukin-6 (IL-6), soluble triggering receptor expressed on myeloid (sTREM) cells, eotaxin-1, and fatty acid-binding protein (FABP) concentrations were tested in 30 plasma samples. Results The concentration of IL-6, eotaxin-1, FABP, and LPS was similar between schistosome-infected and uninfected children. The schistosome-infected children had higher median levels of sTREM and sCD23 as compared to uninfected children, 119.0 (29.9–208.9) versus 10.7 (0.0–73.4) (p = 0.046) and 2,549.0 (1,899.0–3,356.0) vs. 2,035.0 (1,448.0–2,939.0) (p = 0.05), respectively. In addition, sTREM was positively correlated with egg density (p = 0.017). Conclusion Our data show that active schistosomiasis per se is associated with elevated levels of sTREM and sCD23. sTREM has potential diagnostic and prognostic values. However, these biomarkers did not distinguish between children with low egg burden and uninfected children.